(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the importance of the light industry sector in the development of the regional economy and the issues of increasing its export potential. In particular, the role of textile and garment industries in the regional economy, export opportunities, and existing problems are examined using the example of the Bukhara region. The study substantiates ways to increase export volumes by expanding opportunities for exporting light industry products to foreign markets, improving production efficiency, and introducing modern technologies. In addition, scientific proposals and recommendations have been developed to increase employment, attract investment, and expand the geography of exports through the development of light industry enterprises in the regions.